Analisis Keberhasilan Penerapan E-Learning di Fakultas Teknik Universitas Riau: Analysis of The Success of E-Learning Application in Faculty of Engineering Riau University - Neni Seliana; Arif Imam Suroso; Lilik Noor Yuliati (School of Business, Bogor Agricultural University (SB-IPB), 2020)
E-learning is a learning system that uses information systems and internet and intranet technology. E-learning is one of the learning tools in the era of the technological revolution 4.0 which is one of the programs of the Ministry of Higher Education Research. Higher education institutions in Indonesia have used e-learning in learning activities. This study aims to evaluate, and analyze the factors that influence the successful use of e-learning in the Faculty of Engineering. Respondent in this Research consisted of 330 people consisting of students and lecturers of the Faculty of Engineering who use e-learning. Sampling is done by accidental sampling method. The model used in the study is the successful model of Delone and McLean using descriptive analysis and Structural Equation Models (SEM) analysis using SMARTPLS 2.0. The results showed the high level of success in using e-learning at Engineering Faculty at Riau University in semantic succes level, then technical success level, and effectiveness success level. Factors that influencing the Engineering Faculty of Riau University are information quality and service quality. Keywords: delon and mclean, e-learning, SEM, Faculty of Engineering University of Riau